Variations among experienced surgeons in cancer control after open radical prostatectomy - Bianco, Fernando J. (2010)
PURPOSE: It has been demonstrated that complications and functional outcomes after prostate surgery vary between different surgeons to a greater extent than might be accounted for by chance. This type of excessive variation is known as “heterogeneity.” In this study, we explored whether there is also heterogeneity among high-volume surgeons with respect to cancer control after surgery. PATIENTS AND METHODS: The study cohort consisted of 7,725 patients with clinically localized prostate cancer treated by open radical prostatectomy at four major US academic medical centers 1987 – 2003 by one of 54 surgeons. We defined biochemical recurrence by a serum PSA level ≥ 0.4 ng/mL followed by a subsequent higher PSA level. Multivariable random effects models were used to evaluate the heterogeneity in prostate cancer recurrence between surgeons, after adjustment for case-mix (PSA, pathological stage and grade), year of surgery and surgeon experience. RESULTS: We found statistically significant heterogeneity in prostate cancer recurrence rates (p=0.002) independent of surgeon experience. Seven experienced surgeons in our series had adjusted five-year prostate cancer recurrence rates less than 10%, while another five experienced surgeons had rates that exceed 25%. Significant heterogeneity remained in sensitivity analyses adjusting for possible differences in follow-up, patient selection and stage migration. CONCLUSIONS: A patient's risk of recurrence may differ depending on which of two surgeons he sees, even if they have similar levels of experience. Surgical randomized trials are imperative to determine and characterize the roots of these variations